Correlation of Potassium Intake and Physical Activity with Blood Pressure in Hypertensive Patients at Puskesmas Kedungmundu Semarang - Karimulloh, Ali Akbar; Ulvie, Yuliana Noor Setiawati; Kusuma, Hapsari Sulistya; Sulistiani, Ria Purniawan (Universitas Negeri Semarang, 2022)
Hypertension or high blood pressure is a major risk factor of cardiovascular diseases which is a prime contributor to deaths worldwide. The purpose of this study was to determine the relationship between potassium intake and physical activity with blood pressure in hypertensive patients. A total of 47 samples participated in this analytical cross-sectional study and provided data about potassium intake and physical activity through interviews using Semiquantitative Food Frequency Questionnaire (SQFFQ). Blood pressure data were obtained from medical records. Data were analyzed with Rank Spearman correlation test. The results showed 4 (8.5%) subjects had sufficient potassium intake, while for the remaining 91.5% didn’t meet their dietary potassium requirements. Most of the participants (87.2%) had low physical activity levels. No correlation was found between potassium intake and systolic blood pressure (p=0.261) while a statistically significant relationship with diastolic blood pressure (p=0.026). Physical activity levels showed significant correlation with both systolic (p=0.047) and diastolic (p=-0.022). In conclusion, no association was found between potassium intake and systolic blood pressure but the opposite was observed for diastolic blood pressure. Physical activity levels showed significant correlations with systolic and diastolic blood pressures.